(untitled) (Research, Society and Development, 2022)
Report of a patient with type 1 diabetes mellitus presenting with severe diabetic ketoacidosis associate with SARS-CoV-2 infection under treatment in an Intensive Care Unit at a Hospital in the city of Manaus-AM. A 50-year-old male patient with previous diagnosis of Psoriasis Vulgaris and Type 1 Diabetes Mellitus, in regular use of Insulin, presented a flu-like syndrome manifested by fever, dyspnea, myalgia and anosmia. After five days evolved with worsening of breathing pattern associated with a decline in general condition. Subsequently diagnosed with Severe Ketoacidosis associated with SARS-CoV-2 infection, then admitted to an Intensive Care Unit bed, being discharged after 08 days of hospitalization with substantial improvement in the respiratory condition and resolution of ketoacidosis. The relationship between SARS-CoV-2 infection and the development of ketoacidosis in diabetic patients became clear, as well as the association between ICU care and better outcome.